Kewenangan Penyidik Kepolisian untuk Melakukan Penyidikan terhadap Kasus Pidana Keterangan Palsu di Persidangan Pengadilan - Priscilla Tazia Sulaiman (Lentera Hukum, 2018)
Article 160, paragraph (4), Act Number 8, Year 1981, Code of Criminal Procedure states that witnesses are obliged to take an oath in accordance with their religion, before providing a statement in courts. It is aimed to prevent witnesses from providing a fake statement, as it is strictly prohibited in Article 174 Code of Criminal Procedure and Article 24, Criminal Code. In practice, it has resulted in contentious views of the application of such articles. In one regard, the procedure settles the problem of fake statements, as it does not require a report or an investigation, but only the ruling of judges. In contrast, another argument states that it does not require the ruling of judges, so that witnesses can be reported to police for investigation. This article revisits the power of police to investigate a fake statement in courts. By using legal research, the results of the study show that Article 242 Criminal Code remains to be applied in cases of fake statements, with the absence of a judge’s ruling. Therefore, police remains to be granted the power to investigate fake statements. Keywords: Investigation, Witness, Fake Statement